Coated glass, laminated glass and preparation method thereof
By using the CuxNiy layer as the upper dielectric layer in the coating structure of infrared reflective glass, the problem of insufficient oxidation resistance and corrosion resistance of the metal layer is solved, and a more stable coating structure and neutral color perspective effect is achieved, improving the performance and aesthetics of the product.
Patent Information
- Application Number
- CN202411917468.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The metal layer of existing infrared reflective glass has poor oxidation resistance and corrosion resistance, which leads to problems such as glass curtain walls and automobile front windshields that are prone to metal layer degeneration and perspective color green during use.
The CuxNiy layer is used as the upper dielectric layer of the coating structure. By combining the lower dielectric layer, metal layer and upper dielectric layer in the laminated structure, the anti-oxidation and corrosion resistance of the metal layer are enhanced, and the perspective color of the laminated glass is improved to maintain a neutral color.
It effectively improves the anti-oxidation and corrosion resistance of the coating structure, avoids the fall of the metal layer and the degradation of optical performance, and improves the perspective color of the glass, improving the aesthetics and user experience of the product.
Smart Images

Figure CN119704805A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of glass technology, and in particular to a coated glass, a laminated glass and a preparation method thereof. Background Art
[0002] Infrared reflective glass generally has thermal properties such as energy saving, heat insulation, and sun shading, and is deeply loved by customers. It is mainly used as energy-saving glass for glass curtain walls and car windshields. There are two main technologies for infrared reflective glass. One is to use silver as the metal layer of the low-emissivity film layer, but the disadvantage is that the oxidation resistance is poor. The other is to use silver alloy as the low-emissivity metal layer. For example, CN110642529A proposes to use silver-copper / silver-platinum alloy as the metal layer to improve the oxidation resistance of the infrared reflective film system. However, the doping amount of copper / platinum is generally small, and the product's transmittance color cannot be improved. Summary of the invention
[0003] The embodiments of the present application provide a coated glass, a laminated glass and a preparation method thereof, which can make the coated structure have better anti-oxidation performance and make the perspective color of the coated glass neutral.
[0004] In a first aspect, the present application provides a coated glass, comprising:
[0005] a first substrate; and
[0006] A coating structure, wherein the coating structure includes at least one functional stack, each of the functional stacks includes a lower dielectric layer, a metal layer and an upper dielectric layer stacked in sequence, the lower dielectric layer is located on the side of the metal layer facing the first substrate, the metal layer is connected to the surface of the lower dielectric layer facing away from the first substrate, and the upper dielectric layer includes a CuxNiy layer, and the CuxNiy layer is connected to the surface of the metal layer facing away from the lower dielectric layer.
[0007] In this embodiment, the CuxNiy layer is used as the upper dielectric layer of the metal layer, which can solve the problem that the metal layer is easily oxidized and corroded in the atmospheric environment and prevent the metal layer from losing the function of reflecting energy.
[0008] In addition, the bonding force between the CuxNiy layer and the metal layer is strong, so the upper dielectric layer and the metal layer are not easy to fall off, thus preventing the unstable lamination state of the coating structure from affecting the optical properties of the laminated glass.
[0009] In addition, in the common coated glass with NiCr as the upper dielectric layer, the edge of the glass is prone to redness. Using the CuxNiy layer instead of the NiCr layer can improve the perspective color of the coated glass so that the perspective color of the coated glass can remain neutral, thereby beautifying the appearance of the coated glass and bringing a better user experience.
[0010] In a possible implementation, in an alcohol wiping performance test, the coating structure is wiped with alcohol multiple times, and when the coating structure peels off, the number of alcohol wiping times is greater than or equal to 50 times.
[0011] In a possible implementation manner, in the CuxNiy layer, the ratio of X to Y is between 11 / 9 and 17 / 3.
[0012] In a possible implementation manner, the extinction coefficient K value of the CuxNiy layer is between 2.70 and 3.10.
[0013] In a possible implementation manner, the metal layer is a silver layer.
[0014] In one possible implementation, the upper dielectric layer includes a first dielectric sublayer and a second dielectric sublayer, the first dielectric sublayer is connected to the metal layer, the second dielectric sublayer is connected to a side of the first dielectric sublayer away from the metal layer, the material of the first dielectric sublayer includes the CuxNiy layer, and the material of the second dielectric sublayer includes at least one of AZO, Ti alloy, NbOx, TiOx, NiCr, NiCrOx, ZnAlOx, ZnOx, and SnOx.
[0015] In a possible implementation manner, the lower dielectric layer includes at least one of AZO, Ti alloy, NbOx, TiOx, NiCr, NiCrOx, ZnAlOx, ZnOx, and SnOx.
[0016] In a possible implementation manner, the number of the functional stacks is at least two, and at least two of the functional stacks are stacked;
[0017] The coating structure also includes an intermediate layer, which is located between two adjacent functional stacks, and the material of the intermediate layer includes at least one of ZnSnOx, SiAlZrNx, SiAlNx, SiNx, SiZrNx, ZnOx, AZO, ZnAlOx, ITO, and ZrOx.
[0018] In a possible implementation, the coating structure further includes an adhesion layer, wherein the adhesion layer is connected between the first substrate and one of the functional stacks, and the material of the adhesion layer includes at least one of SiAlZrNx, ZrOx, NbOx, SiNx, ZnSnOx, and SiZrNx.
[0019] In a possible implementation manner, the coating structure further includes a first protective layer, the first protective layer is located between the functional stack and the outermost protective layer, and the material of the first protective layer includes ZnSnOx.
[0020] In a possible implementation manner, the coating structure further includes a second protective layer, the second protective layer is located between the first protective layer and the outermost protective layer, and the material of the second protective layer includes TiOx.
[0021] In a second aspect, the present application also provides a laminated glass, comprising a second substrate, an adhesive layer and the coated glass as described above, wherein the adhesive layer is connected between the second substrate and the coated glass, and the coating structure is located between the first substrate and the second substrate.
[0022] In a possible implementation, the laminated glass has a reflection color Lab value for light incident at an incident angle of 8°, and the value a satisfies: a≥-3; the laminated glass has a reflection color Lab value for light incident at an incident angle of 60°, and the value a satisfies: a≥-3.
[0023] In a possible implementation manner, the haze value of the laminated glass is ≤5%.
[0024] In a third aspect, the present application also provides a method for preparing laminated glass, comprising:
[0025] Providing a first substrate:
[0026] forming a coating structure on the surface of the first substrate by a magnetron sputtering process to form coated glass;
[0027] The coating structure includes at least one functional stack, each of which includes a lower dielectric layer, a metal layer and an upper dielectric layer stacked in sequence, the lower dielectric layer covers the surface of the first substrate, the metal layer is connected to the surface of the lower dielectric layer facing away from the first substrate, and the upper dielectric layer includes a CuxNiy layer, and the CuxNiy layer is connected to the surface of the metal layer facing away from the lower dielectric layer.
[0028] In a possible implementation manner, after forming a coating structure on the surface of the first substrate by a magnetron sputtering process, the preparation method further includes:
[0029] providing a second substrate;
[0030] The second substrate and the coated glass are connected to form a stacked structure through an adhesive layer, wherein the stacked structure has a reflection color Lab value for light incident at an incident angle of 8°, and the a value satisfies: a≥-2; the stacked structure has a reflection color Lab value for light incident at an incident angle of 60°, and the a value satisfies: a≥-3;
[0031] The laminated structure is heat-treated and laminated to form laminated glass. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solution of the present application, the drawings required for use in the implementation manner will be briefly introduced below. Obviously, the drawings described below are only some implementation manners of the present application. For ordinary technicians in this field, other drawings can be obtained like these drawings without paying any creative work.
[0033] Figure 1 is a schematic cross-sectional view of a laminated glass provided in an embodiment of the present application;
[0034] Figure 2 yes Figure 1 A schematic cross-sectional view of a first embodiment of the coated glass shown;
[0035] Figure 3 yes Figure 1 A schematic cross-sectional view of a second embodiment of the coated glass shown;
[0036] Figure 4 yes Figure 1 A schematic cross-sectional view of a third embodiment of the coated glass shown;
[0037] Figure 5 It is a schematic flow chart of a method for preparing coated glass provided in an embodiment of the present application.
[0038] Reference numerals:
[0039] Laminated glass 1000, coated glass 1001, bonding layer 1002, second substrate 1003, first substrate 100, coating structure 200, outermost protective layer 280, first laminate 220, second laminate 230, intermediate layer 250, adhesion layer 210, first protective layer 260, second protective layer 270, first lower dielectric layer 221, first metal layer 222, first upper dielectric layer 223, second lower dielectric layer 231, second metal layer 232, second upper dielectric layer 233, third laminate 240, third lower dielectric layer 241, third metal layer 242, third upper dielectric layer 243, first intermediate layer 251, second intermediate layer 252, fourth laminate 290, fourth lower dielectric layer 291, fourth metal layer 292, fourth upper dielectric layer 293, third intermediate layer 253. DETAILED DESCRIPTION
[0040] For ease of understanding, the terms involved in the embodiments of the present application are first explained.
[0041] And / or: It is just a way to describe the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone.
[0042] Multiple: refers to two or more than two.
[0043] Connection: should be understood in a broad sense. For example, A and B are connected, which can be either direct or indirect through an intermediary.
[0044] The specific implementation of the present application will be clearly described below in conjunction with the accompanying drawings.
[0045] See also Figure 1 , Figure 1 1 is a schematic cross-sectional view of a laminated glass 1000 provided in an embodiment of the present application. The laminated glass 1000 comprises a coated glass 1001, an adhesive layer 1002 and a second substrate 1003. The adhesive layer 1002 is connected between the second substrate 1003 and the coated glass 1001. The coated glass 1001 comprises a first substrate 100 and a coating structure 200. The coating structure 200 is disposed on at least one surface of the first substrate 100. Exemplarily, the coating structure 200 is located between the first substrate 100 and the second substrate 1003, that is, the side of the first substrate 100 provided with the coating structure 200 is connected to the adhesive layer 1002.
[0046] It should be noted that Figure 1 The purpose is only to schematically describe the connection relationship between the coated glass 1001, the adhesive layer 1002 and the second substrate 1003, and it does not specifically limit the connection position, specific structure and quantity of each device. The structure shown in the embodiment of the present application does not constitute a specific limitation on the laminated glass 1000. In other embodiments of the present application, the laminated glass 1000 may include Figure 1 More or fewer components may be shown, or some components may be combined or separated, or the components may be arranged differently. Figure 1 The components shown may be implemented in hardware, software or a combination of software and hardware.
[0047] In the present application, the laminated glass 1000 can be installed on a vehicle and used as a windshield, a side window glass, a rear windshield, a sunroof glass, or the like.
[0048] The first substrate 100 and the second substrate 1003 can both be transparent glass or ultra-transparent glass (ultra-white glass). 2 O 3 ) content is low, and the visible light transmittance of ultra-clear glass is greater than or equal to 90%. The total iron content of transparent glass is less than or equal to 0.1%, and the visible light transmittance of transparent glass is greater than or equal to 80%. Calculated by weight percentage, the first substrate 100 and the second substrate 1003 may include 0 to 0.1% of iron oxide (Fe 2 O 3 ), for example, iron oxide (Fe 2 O3 ) content is less than or equal to 0.09%, less than or equal to 0.08%, less than or equal to 0.07%, less than or equal to 0.05%, less than or equal to 0.04%, less than or equal to 0.03%, less than or equal to 0.02%, less than or equal to 0.015% or less than or equal to 0.01%, and even the first substrate 100 and the second substrate 1003 may substantially not contain iron oxide (Fe 2 O 3 ). For example, the first substrate 100 and the second substrate 1003 may be soda-lime-silicon ultra-transparent glass, borosilicate glass or high-aluminum glass.
[0049] The bonding layer 1002 is used to connect the first substrate 100 and the second substrate 1003 to improve the structural strength of the laminated glass 1000 so that it meets the safety standards and regulatory requirements of more scenarios. The material of the bonding layer 1002 can be polyvinyl butyral (PVB), ethylene vinyl acetate (EVA), thermoplastic polyurethane elastomer (TPU) or ionic polymer film (SGP), etc. Exemplarily, the bonding layer 1002 can be a single-layer structure or a multi-layer structure, and the multi-layer structure can be exemplified by a double-layer structure, a three-layer structure, a four-layer structure, a five-layer structure, etc. The bonding layer 1002 can also have other functions, such as providing at least one colored area as a shadow band to reduce the interference of sunlight to the human eye, or adding an infrared absorber to have a sunscreen or heat insulation function, or adding an ultraviolet absorber to have an ultraviolet shielding function, or at least one layer of the multi-layer structure has a higher plasticizer content to have a sound insulation function.
[0050] See also Figure 2 , Figure 2 yes Figure 1 The cross-sectional structure diagram of the first embodiment of the coated glass 1001 is shown. The coated structure 200 includes at least one functional stack (not labeled in the figure). Each functional stack includes a lower dielectric layer (not labeled in the figure), a metal layer (not labeled in the figure) and an upper dielectric layer (not labeled in the figure) stacked in sequence.
[0051] The lower dielectric layer, metal layer and upper dielectric layer in each functional stack can be formed by magnetron sputtering process respectively. In the direction away from the first substrate 100, the lower dielectric layer in the functional stack is located below the metal layer in the functional stack, that is, the lower dielectric layer is closer to the first substrate 100 than the metal layer. The upper dielectric layer in the functional stack is located above the metal layer in the functional stack, that is, the upper dielectric layer in the functional stack is farther away from the first substrate 100 than the metal layer in the functional stack.
[0052] The metal layer has the characteristics of reflecting infrared rays and good conductivity. The coating structure 200 including the metal layer enables the coated glass 1001 and the laminated glass 1000 to have a heat insulation function, thereby significantly reducing the energy consumption of air conditioning and improving the thermal comfort of the driver and passengers. According to the needs of practical applications, the number of metal layers in the coating structure 200 can be exemplified as two, three, four, five or even more. In a possible implementation, the coating structure 200 can also be used as a transparent conductive film. At this time, the laminated glass 1000 has an electric heating function after being powered on, so that the temperature of the laminated glass 1000 can be increased, thereby preventing fogging or defogging, defrosting, deicing and other functions, and improving driving safety. Exemplarily, the power-on voltage of the laminated glass 1000 can be 12V to 380V. Among them, the metal layer can be a silver layer, and the physical thickness of the metal layer is 5nm-20nm (including the endpoint values 5nm and 20nm).
[0053] Infrared reflective glass generally has thermal properties such as energy saving, heat insulation, and sun shading, and is deeply loved by customers. It is mainly used as energy-saving glass for glass curtain walls and car windshields. There are two main technologies for infrared reflective glass. One is to use silver as the metal layer of the low-emissivity film layer, but the disadvantage is that the oxidation resistance is poor. The other is to use silver alloy as the low-emissivity metal layer. For example, CN110642529A proposes to use silver-copper / silver-platinum alloy as the metal layer to improve the oxidation resistance of the infrared reflective film system. However, the doping amount of copper / platinum is generally small, and the product's transmittance color cannot be improved.
[0054] At present, the metal layer of general infrared reflective glass has poor oxidation resistance and corrosion resistance, which makes the metal layer easy to degenerate and fail during the processing of infrared reflective glass. In addition, the metal layer will cause the perspective color of the glass to be green, which is not conducive to aesthetics and safe driving.
[0055] Based on this, the present application adjusts the structure of the upper dielectric layer of the coating structure to improve the anti-oxidation and anti-corrosion properties of the coating structure, and makes the perspective color of the laminated glass neutral, so that the scenery seen through the laminated glass is more natural and beautiful, which is conducive to safe driving.
[0056] The lower dielectric layer covers the surface of the first substrate 100, the metal layer is connected to the surface of the lower dielectric layer away from the first substrate 100, and the upper dielectric layer includes a CuxNiy layer, which is connected to the surface of the metal layer away from the lower dielectric layer.
[0057] In this embodiment, the CuxNiy layer is used as the upper dielectric layer of the metal layer, which can solve the problem that the metal layer is easily oxidized and corroded in the atmospheric environment and prevent the metal layer from losing the function of reflecting energy.
[0058] In addition, the bonding force between the CuxNiy layer and the metal layer is strong, so the upper dielectric layer and the metal layer are not easy to fall off, thus preventing the unstable lamination state of the coating structure from affecting the optical properties of the laminated glass.
[0059] In addition, in the common coated glass with NiCr as the upper dielectric layer, the edge of the glass is prone to redness. Using the CuxNiy layer instead of the NiCr layer can improve the perspective color of the coated glass so that the perspective color of the coated glass can remain neutral, thereby beautifying the appearance of the coated glass and bringing a better user experience.
[0060] In some possible implementations, in the CuxNiy layer, the ratio of X to Y is between 11 / 9 and 17 / 3. Specifically, in the CuxNiy layer, the ratio of Cu to Ni can be 60:40, or 70:30, or 80:20.
[0061] The extinction coefficient K value of the CuxNiy layer is between 2.70 and 3.10.
[0062] In one possible embodiment, the upper dielectric layer includes a first dielectric sublayer and a second dielectric sublayer, the first dielectric sublayer is connected to the metal layer, the second dielectric sublayer is connected to the side of the first dielectric sublayer facing away from the metal layer, the material of the first dielectric sublayer includes a CuxNiy layer, and the material of the second dielectric sublayer includes at least one of AZO, Ti alloy, NbOx, TiOx, NiCr, NiCrOx, ZnAlOx, ZnOx, and SnOx.
[0063] The upper dielectric layer includes at least one of AZO, Ti alloy, NbOx, TiOx, NiCr, NiCrOx, ZnAlOx, ZnOx, SnOx. The thickness of the lower dielectric layer and / or the upper dielectric layer ranges from 5nm to 30nm (including the end values of 5nm and 30nm).
[0064] In each functional stack, the upper dielectric layer is mainly used to protect the metal layer from damage by oxygen ions. The physical thickness of the upper dielectric layer is 5nm-30nm. The upper dielectric layer can be a single film layer or composed of multiple sub-film layers. The lower dielectric layer is mainly used to protect the metal layer from damage by alkali metal ions and to serve as a crystallization seed layer of the metal layer to improve its deposition density.
[0065] In some possible implementations, the coating structure 200 further includes an intermediate layer 250, the intermediate layer 250 is located between two adjacent functional stacks, and the material of the intermediate layer 250 includes at least one of ZnSnOx, SiAlZrNx, SiAlNx, SiNx, SiZrNx, ZnOx, AZO, ZnAlOx, ITO, and ZrOx. The thickness of the intermediate layer 250 is in the range of 30nm-75nm (including the endpoints of 30nm and 75nm).
[0066] In this embodiment, the intermediate layer 250 can improve the flatness of the coating structure 200 and improve the reflection color. These intermediate layers 250 can be a single film layer or composed of multiple sub-film layers.
[0067] In some possible implementations, the coating structure 200 further includes an adhesion layer 210, which is connected between the first substrate 100 and a functional stack, and the material of the adhesion layer 210 includes at least one of SiAlZrNx, ZrOx, NbOx, SiNx, ZnSnOx, and SiZrNx. The thickness of the adhesion layer 210 ranges from 10nm to 40nm (including the endpoints of 10nm and 40nm).
[0068] In this embodiment, the adhesion layer 210 is directly deposited on the surface of the first substrate 100 to reduce or prevent the diffusion of alkali metal ions from the glass into the coating structure 200. It can also increase the adhesion between the coating structure 200 and the surface of the first substrate 100, and help adjust the mechanical properties, optical properties and high-temperature heat treatment properties of the coating structure 200.
[0069] For some possible implementations, please continue to refer to Figure 2 The coating structure 200 further includes a first protective layer 260, which is located between the functional stack and the outermost protective layer 280. The material of the first protective layer 260 includes ZnSnOx. The thickness of the first protective layer 260 ranges from 0 nm to 25 nm (including the end values of 0 nm and 25 nm).
[0070] In some possible implementations, the coating structure 200 further includes a second protective layer 270 and an outermost protective layer 280, wherein the second protective layer 270 is located between the first protective layer 260 and the outermost protective layer 280, and the material of the second protective layer 270 includes TiOx. The thickness of the second protective layer 270 is in the range of 0nm-25nm (including the end values of 0nm and 25nm). Along the thickness direction of the coating structure 200, the adhesion layer 210, a functional stack (the first stack 220), an intermediate layer 250, another functional stack (the second stack 230), the first protective layer 260, the second protective layer 270 and the outermost protective layer 280 are stacked in sequence.
[0071] The outermost protective layer 280 is mainly used to protect the metal layer in the functional stack from corrosion and mechanical damage, and is conducive to adjusting the mechanical properties, optical properties and high-temperature heat treatment properties of the coating structure 200. The outermost protective layer 280 is all the film layers on the outside of the functional stack farthest from the first substrate 100 in the coating structure 200. The outermost protective layer 280 can be a single film layer or composed of multiple sub-film layers. The physical thickness of the outermost protective layer 280 can be between 5nm and 70nm (including the end values of 5nm and 70nm).
[0072] In some embodiments, the material of the outermost protective layer 280 can also be selected from oxides, nitrides or oxynitrides of at least one element among Si, Zn, Mg, Sn, Ti, Nb, Zr, Ni, In, Al, Ce, W, Mo, Sb, and Bi, and specific examples include ZrNx, SiOx, SiOxNy, SiAlZrNx, SiZrNx, SiNx, SiZrOx, SiAlZrOx, etc.
[0073] In the first possible implementation, please continue to refer to Figure 2 The number of functional stacks in the coating structure 200 is two, and the two functional stacks are respectively a first stack 220 and a second stack 230. The first stack 220 includes a first lower dielectric layer 221, a first metal layer 222 and a first upper dielectric layer 223, and the second stack 230 includes a second lower dielectric layer 231, a second metal layer 232 and a second upper dielectric layer 233. The coating structure 200 specifically includes an adhesion layer 210, a first lower dielectric layer 221, a first metal layer 222, a first upper dielectric layer 223, an intermediate layer 250, a second lower dielectric layer 231, a second metal layer 232, a second upper dielectric layer 233, a first protective layer 260, a second protective layer 270 and an outermost protective layer 280, which are stacked in sequence.
[0074] In a second possible implementation, see Figure 3 , Figure 3 yes Figure 1The cross-sectional structure diagram of the second embodiment of the coated glass 1001 is shown. The number of functional stacks in the coating structure 200 is three, and the three functional stacks are respectively the first stack 220, the second stack 230 and the third stack 240. The first stack 220 includes the first lower dielectric layer 221, the first metal layer 222 and the first upper dielectric layer 223. The second stack 230 includes the second lower dielectric layer 231, the second metal layer 232 and the second upper dielectric layer 233. The third stack 240 includes the third lower dielectric layer 241, the third metal layer 242 and the third upper dielectric layer 243. The coating structure 200 also includes two intermediate layers 250, and the two intermediate layers 250 are respectively the first intermediate layer 251 and the second intermediate layer 252. The coating structure 200 specifically includes an adhesion layer 210, a first lower dielectric layer 221, a first metal layer 222, a first upper dielectric layer 223, a first intermediate layer 251, a second lower dielectric layer 231, a second metal layer 232, a second upper dielectric layer 233, a second intermediate layer 252, a third lower dielectric layer 241, a third metal layer 242, a third upper dielectric layer 243, a first protective layer 260, a second protective layer 270 and an outermost protective layer 280, which are stacked in sequence.
[0075] Among them, the thickness of the first metal layer 222, the second metal layer 232 and the third metal layer 242 is between 5nm and 20nm (including the endpoint values of 5nm and 20nm). The thickness of the first upper dielectric layer 223, the first lower dielectric layer 221, the second upper dielectric layer 233, the second lower dielectric layer 231, the third upper dielectric layer 243, and the third lower dielectric layer 241 is between 5nm and 20nm (including the endpoint values of 5nm and 20nm). The thickness of the first intermediate layer 251 and the second intermediate layer 252 is between 30nm and 70nm (including the endpoint values of 30nm and 70nm). The thickness of the adhesion layer 210 is between 10nm and 50nm (including the endpoint values of 10nm and 50nm). The thickness of the first protective layer 260 is between 0-20nm (including the endpoint values of 0 and 20nm). The thickness of the second protective layer 214 is between 0-20nm (including the endpoint values of 0 and 20nm).
[0076] In a third possible implementation, see Figure 4 , Figure 4 yes Figure 1The cross-sectional structure diagram of the third embodiment of the coated glass 1001 is shown. The number of functional stacks in the coating structure 200 is four, and the four functional stacks are respectively the first stack 220, the second stack 230, the third stack 240 and the fourth stack 290. The first stack 220 includes the first lower dielectric layer 221, the first metal layer 222 and the first upper dielectric layer 223. The second stack 230 includes the second lower dielectric layer 231, the second metal layer 232 and the second upper dielectric layer 233. The third stack 240 includes the third lower dielectric layer 241, the third metal layer 242 and the third upper dielectric layer 243. The fourth stack 290 includes the fourth lower dielectric layer 291, the fourth metal layer 292 and the fourth upper dielectric layer 293. The coating structure 200 also includes three intermediate layers 250, and the three intermediate layers 250 are respectively the first intermediate layer 251, the second intermediate layer 252 and the third intermediate layer 253. The coating structure 200 specifically includes an adhesion layer 210, a first lower dielectric layer 221, a first metal layer 222, a first upper dielectric layer 223, a first intermediate layer 251, a second lower dielectric layer 231, a second metal layer 232, a second upper dielectric layer 233, a second intermediate layer 252, a third lower dielectric layer 241, a third metal layer 242, a third upper dielectric layer 243, a third intermediate layer 253, a fourth lower dielectric layer 291, a fourth metal layer 292, a fourth upper dielectric layer 293, a first protective layer 260, a second protective layer 270 and an outermost protective layer 280, which are stacked in sequence.
[0077] In addition to the structure described above, the laminated glass 1000 may also include two coated glasses 1001 and a bonding layer 1002 described above. The two coated glasses 1001 are arranged opposite to each other on one side where the coating structure 200 is provided, and the bonding layer 1002 is connected between the two coating structures 200. The structure of any coated glass 1001 may refer to the above description, and the present application will not elaborate on it here.
[0078] The present application also provides a method for preparing coated glass 1001, wherein the specific structure of coated glass 1001 can be referred to Figure 1-Figure 4 As well as the description in the above question, the improvements on the coated glass 1001 can be applied to the description of the coated glass 1001 above, unless there is any conflict. Figure 5 , Figure 5 1 is a schematic flow chart of a method for preparing a laminated glass 1000 provided in an embodiment of the present application. The preparation method comprises:
[0079] S100: providing a first substrate 100 .
[0080] S200: forming a coating structure 200 on the surface of the first substrate 100 by a magnetron sputtering process to form a coated glass 1001;
[0081] The coating structure 200 includes at least one functional stack, each functional stack includes a lower dielectric layer, a metal layer and an upper dielectric layer stacked in sequence, the lower dielectric layer covers the surface of the first substrate 100, the metal layer is connected to the surface of the lower dielectric layer facing away from the first substrate 100, and the upper dielectric layer includes a CuxNiy layer, and the CuxNiy layer is connected to the surface of the metal layer facing away from the lower dielectric layer.
[0082] In addition, in addition to the above steps, the preparation method may further include:
[0083] S300: providing a second substrate 1003;
[0084] S400: connecting the second substrate 1003 and the coated glass 1001 through the adhesive layer 1002 to form a stacked structure, wherein the stacked structure has a reflection color Lab value for light incident at an incident angle of 8°, and the a value satisfies: a≥-2; the stacked structure has a reflection color Lab value for light incident at an incident angle of 60°, and the a value satisfies: a≥-3;
[0085] S500: The laminated structure is heat-treated and laminated to form laminated glass 1000.
[0086] This application also provides upper dielectric layers of various materials to explore the extinction coefficient K values of various film layers. Please refer to Table 1 for specific test results.
[0087] Table 1. Test structure of extinction coefficient of various material films
[0088]
[0089] From the six film layers in Table 1, it can be seen that the extinction coefficient of the Cu film layer is relatively small compared to the extinction coefficients of the Ni and Cr film layers. During the heating process, the Cu layer absorbs less heat. When the upper dielectric layer is connected to the metal layer (silver layer), the actual heating temperature of the metal layer will be lower. This is because the dielectric layer is close to the metal layer, and the dielectric layer absorbs heat, which will increase the heating temperature of the metal layer. This can reduce the scene where the edge of the coated glass turns red after heating.
[0090] Ni is a "binder" between metals, between metals and non-metals, and between metals and metal oxides. With the presence of Ni, the film adhesion between the metal layer and other film layers can be significantly improved, which is reflected in the subsequent examples and comparative examples in this article.
[0091] Comparative Examples 1-4 and Examples 1-4
[0092] The present application prepares a 2.1 mm thick transparent glass substrate, deposits the film structure of Comparative Examples 1-4 and Examples 1-4 on the surface of the transparent glass substrate by magnetron sputtering process, and measures the optical properties and mechanical properties of the coated glass 1001 test samples of Comparative Examples 1-4 and Examples 1-4 before high-temperature heat treatment, measures the optical properties and mechanical properties of Comparative Examples 1-4 and Examples 1-4 after high-temperature heat treatment, and measures the optical properties and mechanical properties of Comparative Examples 1-4 and Examples 1-4 after glass interlayer treatment, and the measurement results are recorded in Table 2 and Table 3. Among them, the coated glass 1001 test samples of Comparative Examples 1-4 and Examples 1-4 both include two functional laminates.
[0093] Table 2: Measurement results of the coated glass 1001 test samples of Comparative Examples 1-4
[0094]
[0095] From the data in Table 2, it can be seen that in Comparative Example 1, AgCu is used as the first metal layer, and NiCr is used as the first upper dielectric layer and the second upper dielectric layer, and the overall processing performance of the double silver film system is qualified. However, in the optical test of the double silver film system, the laminated glass has a reflection color Lab value for light incident at an incident angle of 8°, and the laminated glass has a reflection color Lab value for light incident at an incident angle of 60°. Before heat treatment and after interlayer, the a values in the 8° and 60° test transmission Lab values are -2.5 and -3.8, -1.9 and -3.7, respectively. The overall perspective field of view is green, and the scenery outside the car seen through the front windshield is covered with a layer of green "filter", which is not aesthetically pleasing and driving safety is insufficient. At the same time, the doping of Cu in the AgCu alloy causes the AgCu alloy to be separated from Ag and Cu when it is recycled and reused, which greatly increases the cost of using the target material.
[0096] In order to solve the problem of greenish perspective vision of laminated glass and high cost of AgCu alloy target in comparative example 1, Ag is used as the first metal layer, Cu and NiCr are used as the first upper dielectric layer, and the thickness of the Cu layer is increased alone to improve the perspective vision color of the double silver film system. In the optical test, the a values of the double silver film system in the 8° and 60° test transmission Lab values before and after heat treatment were -0.9 and -2.3, -0.4 and -2.1, respectively, and the overall perspective vision was neutral. However, due to the poor adhesion of the Ag layer and the Cu layer, the double silver film system was wiped with alcohol 5 times before and after heat treatment, and the film layer had poor mechanical processing resistance.
[0097] In Comparative Example 3, in order to solve the problem of poor film adhesion in Comparative Example 2, the NiCr in the first upper dielectric layer was increased from 0.5nm to 1nm. The double silver film system was stripped after 30 times of alcohol wiping before and after heat treatment, and the film layer's resistance to mechanical processing was alleviated. However, due to the increase in the thickness of the NiCr layer, the dielectric layer absorbed more heat, the actual temperature of the Ag layer during the heating process was increased, and the edge of the front windshield appeared red.
[0098] Comparative Example 4 uses Ag as the first metal layer, and CuNi (Cu:Ni=70:30wt%) as the first upper dielectric layer and the second upper dielectric layer. In the optical test, the a values of the 8° and 60° test transmission Lab values before heat treatment and after interlayer are -0.6 and -2.0, 0 and -1.7 respectively, and the overall perspective field of view is neutral. It is natural to see the scenery outside the car through the front windshield, and the aesthetics and driving safety are improved. However, the haze test before and after heat treatment and after interlayer is unqualified, and the scenery observed through the glass is not clear enough.
[0099] Table 3: Measurement results of the coated glass 1001 test samples of Examples 1-4
[0100]
[0101] From the data in Table 3, we can see that:
[0102] Example 1 uses Ag as the first metal layer, CuNi (Cu:Ni=70:30wt%) as the first upper dielectric layer 223 and the second upper dielectric layer 233, and the overall processing performance of the double silver film system is qualified. In the optical test, the a values of the 8° and 60° test transmission Lab values before and after heat treatment and interlayer are -0.8 and -2.2, -0.3 and -2.0 respectively, and the overall perspective field of view is neutral color. It is natural to see the scenery outside the car through the laminated glass 1000, and the aesthetics and driving safety are improved. At the same time, the cost of CuNi alloy is lower than that of AgCu alloy, which reduces the cost of recycling and reusing the target material. However, the price of Ag in the AgCu alloy is relatively expensive at present, and Ag needs to be separated and then replenished with AgCu ratio to be processed into a new target material, and the separation and processing fees, and the fees for replenishing Ag and Cu at market prices are charged.
[0103] Example 2 uses Ag as the first metal layer, CuNi (Cu:Ni=80:20wt%) as the first upper dielectric layer 223 and the second upper dielectric layer 233, and the overall processing performance of the double silver film system is qualified. In the optical test, the a values of the 8° and 60° test transmission Lab values before and after heat treatment are -0.6 and -2.0, -0.1 and -1.8 respectively, and the overall perspective field of view is neutral color. It is natural to see the scenery outside the car through the laminated glass 1000, and the aesthetics and driving safety are improved. At the same time, the cost of CuNi alloy is lower than that of AgCu alloy, which reduces the cost of using the target material.
[0104] Example 3 uses Ag as the first metal layer, CuNi (Cu:Ni=60:40wt%) as the first upper dielectric layer 223 and the second upper dielectric layer 233, and the overall processing performance of the double silver film system is qualified. In the optical test, the a values of the 8° and 60° test transmission Lab values before heat treatment and after interlayer are -1.0 and -2.4, -0.5 and -2.2 respectively, and the overall perspective field of view is neutral color. It is natural to see the scenery outside the car through the laminated glass 1000, and the aesthetics and driving safety are improved. At the same time, the cost of CuNi alloy is lower than that of AgCu alloy, which reduces the cost of using the target material.
[0105] Example 4 uses Ag as the first metal layer, CuNi (Cu:Ni=65:25wt%) as the first upper dielectric layer 223 and the second upper dielectric layer 233, and the overall processing performance of the double silver film system is qualified. In the optical test, the a values of the 8° and 60° test transmission Lab values before heat treatment and after interlayer are -0.7 and -2.1, -0.2 and -1.9 respectively, and the overall perspective field of view is neutral color. It is natural to see the scenery outside the car through the laminated glass 1000, and the aesthetics and driving safety are improved. At the same time, the cost of CuNi alloy is lower than that of AgCu alloy, which reduces the cost of using the target material.
[0106] Comparative Example 5 and Examples 5-7
[0107] The present application prepares a 2.1 mm thick transparent glass substrate, deposits the film structure of Comparative Example 5 and Examples 5-7 on the surface of the transparent glass substrate by magnetron sputtering process, and measures the optical properties and mechanical properties of the coated glass 1001 test samples of Comparative Example 5 and Examples 5-7 before high temperature heat treatment, the optical properties and mechanical properties of Comparative Example 5 and Examples 5-7 after high temperature heat treatment, and the optical properties and mechanical properties of Comparative Example 5 and Examples 5-7 after glass interlayer treatment, and the measurement results are recorded in Table 2 and Table 3. Among them, the coated glass 1001 test samples of Comparative Example 5 and Examples 5-7 both include two functional laminates.
[0108] Table 4: Measurement results of the coated glass 1001 test samples of Comparative Example 5 and Examples 5-7
[0109]
[0110] From Table 4, we can see that:
[0111] Comparative Example 5 uses AgCu as the first metal layer, NiCr as the first upper dielectric layer, the second upper dielectric layer, and the third upper dielectric layer, and the overall processing performance of the three-silver film system is qualified. However, in the optical test, the a values of the three-silver film system in the 8° and 60° test transmission Lab values before and after heat treatment are -3.0 and -4.5, -3.7 and -3.8 respectively. The overall perspective field of view is green, and the sky seen through the skylight glass has a layer of green "filter", which is not aesthetically pleasing. The three-silver film system has an anti-oxidation time of only 252h before heat treatment, and is easily oxidized and corroded. At the same time, the doping of Cu in the AgCu alloy causes the AgCu alloy to be separated from Ag and Cu when it is recycled and reused, which greatly increases the cost of using the target material.
[0112] Example 5 uses Ag as the first metal layer, and CuNi (Cu:Ni=70:30wt%) replaces NiCr (Ni:Cr=80:20wt%) as the first upper dielectric layer 223. The overall processing performance of the three silver film systems is qualified, and the anti-oxidation time is increased from 252h to 306h, and the film layer's anti-oxidation and corrosion resistance are improved. In the optical test, the a values of the 8° and 60° test transmission Lab values before and after heat treatment are 0.4 and -0.2, -2.2 and -2.6, respectively. The overall perspective field of view is neutral, and it is natural to see the sky through the laminated glass 1000, and the aesthetics is improved. At the same time, the cost of CuNi alloy is lower than that of the currently used AgCu alloy, which reduces the cost of target material recycling and reuse.
[0113] Example 6 uses Ag as the metal layer, and CuNi (Cu:Ni=70:30wt%) replaces NiCr (Ni:Cr=80:20wt%) as the first upper dielectric layer 223 and the second upper dielectric layer 233. The overall processing performance of the three silver film systems is qualified, and the anti-oxidation time is increased from 252h to 450h, and the film layer's anti-oxidation and corrosion resistance are improved. In the optical test, the a values of the 8° and 60° test transmission Lab values before and after heat treatment are 0.4 and -0.4, -2.2 and -2.6, respectively. The overall perspective field of view is neutral, and it is natural to see the sky through the laminated glass 1000, and the aesthetics is improved. At the same time, the cost of CuNi alloy is lower than that of AgCu alloy, which reduces the cost of target recycling and reuse.
[0114] Example 7 uses Ag as the metal layer, and CuNi (Cu:Ni=70:30wt%) replaces NiCr (Ni:Cr=80:20wt%) as the first upper dielectric layer 223, the second upper dielectric layer 233, and the third upper dielectric layer 243. The overall processing performance of the three silver film systems is qualified, and the anti-oxidation time is increased from 252h to 521h, and the film layer's anti-oxidation and corrosion resistance are improved. In the optical test, the a values of the 8° and 60° test transmission Lab values before and after heat treatment are 0.5 and -0.4, -2.3 and -2.7, respectively. The overall perspective field of view is neutral, and it is natural to see the sky through the laminated glass 1000, and the aesthetics is improved. At the same time, the cost of CuNi alloy is lower than that of AgCu alloy, which reduces the cost of target material recycling and reuse.
[0115] Table 5: Measurement results of the coated glass 1001 test samples of Examples 8-10
[0116]
[0117] From Table 5, we can see that:
[0118] Example 8 uses Ag as the metal layer, and CuNi (Cu:Ni=60:40wt%) replaces NiCr (Ni:Cr=80:20wt%) as the first upper dielectric layer 223, the second upper dielectric layer 233, and the third upper dielectric layer 243. The overall processing performance of the three silver film systems is qualified, and the anti-oxidation time is increased from 252h to 543h, and the film layer's anti-oxidation and corrosion resistance are improved. In the optical test, the a values in the 8° and 60° test transmission Lab values before and after heat treatment are 0.7 and -0.2, -2.1 and -2.5, respectively. The overall perspective field of view is neutral, and it is natural to see the sky through the laminated glass 1000, and the aesthetics is improved. At the same time, the cost of CuNi alloy is lower than that of AgCu alloy, which reduces the cost of target material recycling and reuse.
[0119] Example 9 uses Ag as the metal layer, and CuNi (Cu:Ni=75:15wt%) replaces NiCr (Ni:Cr=80:20wt%) as the first upper dielectric layer 223, the second upper dielectric layer 233, and the third upper dielectric layer 243. The overall processing performance of the three silver film systems is qualified, and the anti-oxidation time is increased from 252h to 507h, and the film layer's anti-oxidation and corrosion resistance are improved. In the optical test, the a values in the 8° and 60° test transmission Lab values before and after heat treatment are 0.4 and -0.5, -2.3 and -2.7, respectively. The overall perspective field of view is neutral, and it is natural to see the sky through the laminated glass 1000, and the aesthetics is improved. At the same time, the cost of CuNi alloy is lower than that of AgCu alloy, which reduces the cost of target material recycling and reuse.
[0120] Example 10 uses Ag as the metal layer, and CuNi (Cu:Ni=80:20wt%) replaces NiCr (Ni:Cr=80:20wt%) as the first upper dielectric layer 223, the second upper dielectric layer 233, and the third upper dielectric layer 243. The overall processing performance of the three silver film systems is qualified, and the anti-oxidation time is increased from 252h to 485h, and the film layer's anti-oxidation and corrosion resistance are improved. In the optical test, the a values in the 8° and 60° test transmission Lab values before and after heat treatment are 0.3 and -0.6, -2.4 and -2.8, respectively. The overall perspective field of view is neutral color, and it is natural to see the sky through the laminated glass 1000, and the aesthetics is improved. At the same time, the cost of CuNi alloy is lower than that of AgCu alloy, which reduces the cost of target material recycling and reuse.
[0121] To summarize the above embodiments, it can be known that before the laminated glass is heat treated, the laminated structure has a reflection color Lab value for light incident at an incident angle of 8°, and the a value satisfies: a≥-2; the laminated structure has a reflection color Lab value for light incident at an incident angle of 60°, and the a value satisfies: a≥-3.
[0122] After the laminated glass is heat treated, the laminated glass has a Lab value of reflected color transmission optical test for light incident at an incident angle of 8°, and the a value satisfies: a value ≥ -3. The laminated glass has a Lab value of reflected color transmission optical test for light incident at an incident angle of 60°, and the a value satisfies: a value ≥ -3.
[0123] The haze test of the embodiments provided in this application is all qualified, which means the haze value of the coated glass is ≤5%.
[0124] In this embodiment, when the coated glass is applied to a vehicle, low haze means that the coated glass has high transparency and improved imaging effect, which is beneficial to improving the clarity of the coated glass, thereby providing a clearer field of view for the driver or passengers.
[0125] The embodiments of the present application are introduced in detail above. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method and core idea of the present application. At the same time, for general technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. A coated glass, characterized in that: include: a first substrate; and A coating structure, wherein the coating structure is arranged on the surface of a first substrate, the coating structure includes at least one functional stack, each of the functional stack includes a lower dielectric layer, a metal layer and an upper dielectric layer stacked in sequence, the lower dielectric layer is located on the side of the metal layer facing the first substrate, the metal layer is connected to the surface of the lower dielectric layer facing away from the first substrate, and the upper dielectric layer includes a CuxNiy layer, and the CuxNiy layer is connected to the surface of the metal layer facing away from the lower dielectric layer.
2. The coated glass according to claim 1, characterized in that: In the alcohol wiping performance test, the coating structure is wiped with alcohol for multiple times. When the coating structure peels off, the number of alcohol wiping is greater than or equal to 50 times.
3. The coated glass according to claim 1, characterized in that: In the CuxNiy layer, the ratio of X to Y is between 11 / 9 and 17 / 3.
4. The coated glass according to claim 2, characterized in that: The extinction coefficient K value of the CuxNiy layer is between 2.70 and 3.
10.
5. The coated glass according to any one of claims 1 to 4, characterized in that: The metal layer is a silver layer.
6. The coated glass according to claim 5, characterized in that: The upper dielectric layer includes a first dielectric sublayer and a second dielectric sublayer, the first dielectric sublayer is connected to the metal layer, the second dielectric sublayer is connected to the side of the first dielectric sublayer away from the metal layer, the material of the first dielectric sublayer includes the CuxNiy layer, and the material of the second dielectric sublayer includes at least one of AZO, Ti alloy, NbOx, TiOx, NiCr, NiCrOx, ZnAlOx, ZnOx, and SnOx.
7. The coated glass according to claim 5, characterized in that: The lower dielectric layer includes at least one of AZO, Ti alloy, NbOx, TiOx, NiCr, NiCrOx, ZnAlOx, ZnOx, and SnOx.
8. The coated glass according to any one of claims 1 to 4, characterized in that: The number of the functional stacks is at least two, and at least two of the functional stacks are stacked; The coating structure also includes an intermediate layer, which is located between two adjacent functional stacks, and the material of the intermediate layer includes at least one of ZnSnOx, SiAlZrNx, SiAlNx, SiNx, SiZrNx, ZnOx, AZO, ZnAlOx, ITO, and ZrOx.
9. The coated glass according to any one of claims 1 to 4, characterized in that: The coating structure also includes an adhesion layer, which is connected between the first substrate and one of the functional stacks, and the material of the adhesion layer includes at least one of SiAlZrNx, ZrOx, NbOx, SiNx, ZnSnOx, and SiZrNx.
10. The coated glass according to any one of claims 1 to 4, characterized in that: The coating structure further includes a first protective layer, which is located between the functional stack and the outermost protective layer, and the material of the first protective layer includes ZnSnOx.
11. The coated glass according to claim 10, characterized in that: The coating structure further includes a second protective layer, which is located between the first protective layer and the outermost protective layer, and the material of the second protective layer includes TiOx.
12. A laminated glass, characterized in that: It comprises a second substrate, an adhesive layer and the coated glass according to any one of claims 1 to 11, wherein the adhesive layer is connected between the second substrate and the coated glass, and the coating structure is located between the first substrate and the second substrate.
13. The laminated glass according to claim 12, characterized in that: The laminated glass has a reflection color Lab value for light incident at an incident angle of 8°, and the a value satisfies: a≥-3. The laminated glass has a reflection color Lab value for light incident at an incident angle of 60°, and the a value satisfies: a≥-3.
14. The laminated glass according to claim 12 or 13, characterized in that: The haze value of the laminated glass is ≤5%.
15. A method for preparing laminated glass, characterized in that: include: Providing a first substrate: forming a coating structure on the surface of the first substrate by a magnetron sputtering process to form coated glass; The coating structure includes at least one functional stack, each of which includes a lower dielectric layer, a metal layer and an upper dielectric layer stacked in sequence, the lower dielectric layer covers the surface of the first substrate, the metal layer is connected to the surface of the lower dielectric layer facing away from the first substrate, and the upper dielectric layer includes a CuxNiy layer, and the CuxNiy layer is connected to the surface of the metal layer facing away from the lower dielectric layer.
16. The preparation method according to claim 15, characterized in that: After forming a coating structure on the surface of the first substrate by a magnetron sputtering process, the preparation method further comprises: providing a second substrate; The second substrate and the coated glass are connected to form a stacked structure through an adhesive layer, wherein the stacked structure has a reflection color Lab value for light incident at an incident angle of 8°, and the a value satisfies: a≥-2; the stacked structure has a reflection color Lab value for light incident at an incident angle of 60°, and the a value satisfies: a≥-3; The laminated structure is heat-treated and laminated to form laminated glass.
Citation Information
Patent Citations
Window glass with silver alloy functional layer
CN110642529A
Method for preparing novel copper alloy material layer and film
CN103556120A
Solar control glazing comprising a layer of an alloy containing NiCu
CN103857639A
High-transparency low-reflection double-silver low-radiation film plating glass and preparation method thereof
CN108328942A
Neutral gray low-emissivity coated glass
CN112645607A